Out of the cycle: Impact of cell cycle aberrations on cancer metabolism and metastasis. Issue 8 (26th September 2022) - Cheung, Alvin Ho‐Kwan; Hui, Chris Ho‐Lam; Wong, Kit Yee; Liu, Xiaoli; Chen, Bonan; Kang, Wei; To, Ka Fai
Abstract: The use of cell cycle inhibitors has necessitated a better understanding of the cell cycle in tumor biology to optimize the therapeutic approach. Cell cycle aberrations are common in cancers, and it is increasingly acknowledged that these aberrations exert oncogenic effects beyond the cell cycle. Multiple facets such as cancer metabolism, immunity and metastasis are also affected, all of which are beyond the effect of cell proliferation alone. This review comprehensively summarized the important recent findings and advances in these interrelated processes. In cancer metabolism, cell cycle regulators can modulate various pathways in aerobic glycolysis, glucose uptake and gluconeogenesis, mainly through transcriptional regulation and kinase activities. Amino acid metabolism is also regulated through cell cycle progression. On cancer metastasis, metabolic plasticity, immune evasion, tumor microenvironment adaptation and metastatic site colonization are intricately related to the cell cycle, with distinct regulatory mechanisms at each step of invasion and dissemination. Throughout the synthesis of current understanding, knowledge gaps and limitations in the literature are also highlighted, as are new therapeutic approaches such as combinational therapy and challenges in tackling emerging targeted therapy resistance. A greater understanding of how the cell cycle modulates diverse aspects of cancer biology can hopefully shed light on identifying new molecular targets by harnessing the vast potential of the cell cycle. Abstract :